isolasi dan identifikasi jamur endofit pada tanaman moringa (moringa oleifera Lam.) - Hasnadhiazahra Rohadi; Nuraeni Ekowati; Moh Ilyas (Fakultas Biologi Universitas Jenderal Soedirman, 2019)
Moringa oleifera Lam. is a small, perennial tree which belongs to moringaceae family. This plant is widely known for their nutritional and medicinal purposes. They can associate with microorganisms showing beneficial symbiosis called as endophytic microorganism. Endophytic fungi is microorganism capable of living within the plant tissues without harming their host. This study was aimed for obtaining pure culture of fungal endophytes from M. oleifera and then identifying them based on morphological identification. The morphological identification was done by observing both macro- and micro- morphological characteristics of the endophytic fungi. Twenty endophytic fungi were isolated from lamina, petiole and stem of M. oleifera. The genus obtained were Cladosporium, Colletotrichum, Fusarium, Phomopsis, Phyllosticta, white mycelia sterilia and black mycelia sterilia (Dematiaceae). Keywords: endophytic fungi; identification; isolation; morphology; Moringa oleifera Lam.